2020
DOI: 10.1016/j.accpm.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

ICU outcomes of COVID-19 critically ill patients: An international comparative study

Abstract: Coronavirus disease (COVID-19) caused by the new coronavirus SARS-CoV-2 has hit the world as a global pandemic of an unprecedented scale. COVID-19 has become one of the major causes of death worldwide. It is estimated that around 5% of cases are critically ill, requiring intensive care unit (ICU) admission. As of June 29, 2020, United Arab Emirates counts 47,797 cases, with 313 deaths [1]. The observed ICU mortality rate of COVID-19 is highly variable [2-5]. Also, no studies have reported the ICU outcomes of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…In a study conducted by Yang et al [17], it was shown that there was a mortality rate of 61.5% among 52 ICU patients with COVID-19. In larger series, like multiple studies from Italy, Spain and the USA, mortality rates range from approximately 22% to 61% [20]. Nadeem et al [20] state that international differences might be explained by the fact that in some countries the pandemic arrived later.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In a study conducted by Yang et al [17], it was shown that there was a mortality rate of 61.5% among 52 ICU patients with COVID-19. In larger series, like multiple studies from Italy, Spain and the USA, mortality rates range from approximately 22% to 61% [20]. Nadeem et al [20] state that international differences might be explained by the fact that in some countries the pandemic arrived later.…”
Section: Discussionmentioning
confidence: 94%
“…In larger series, like multiple studies from Italy, Spain and the USA, mortality rates range from approximately 22% to 61% [20]. Nadeem et al [20] state that international differences might be explained by the fact that in some countries the pandemic arrived later. This might have given them more time to prepare, resulting in an improvement of ICU care over time for patients with COVID-19.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Severe acute respiratory syndrome coronavirus-2 (SAR-CoV-2) responsible for the coronavirus disease 2019 (COVID-19) has hit the world as a global pandemic at an unparalleled scale, causing considerable morbidity and mortality [ 1 , 2 , 3 , 4 ]. Most people with COVID-19 have only mild or uncomplicated disease.…”
Section: Introductionmentioning
confidence: 99%